Influence of converting forestland to tea plantation on soil preferential flow occurrence in subtropical hillslopes of Three Gorges Reservoir Area, China - Jiapan Xu; Xue Shen; Muxing Liu; Jun Zhang; Qian Yang; Jun Yi; Shenglong Li; Chongfa Cai (Journal of Hydrology: Regional Studies, 2025)
Study region: Three Gorges Reservoir Area, China Study focus: Soil preferential flow (PF) is a special but important pattern of water infiltration. However, the understanding of how the PF occurrence changes following land-use conversion remains unclear, especially in subtropical hilly and mountainous regions where large areas of forest have been cleared for tea cultivation driven by economic interests. From 2022 to 2024, soil moisture data were acquired from five soil depths across various positions (upslope, mid-slope, and downslope) on two hillslopes with different land-use types (forestland, FL; tea plantation, TP). New hydrological insights for the region: This study investigated 105 rainfall events, during which PF was identified by soil moisture response sequence to rainfall across soil layers. On average, the frequency of PF occurrences (FPF) and proportion of soil water storage from PF events (PSWS) for FL were 7.9 % and 40.8 %, respectively, higher than those for TP, which were 7.1 % and 35.4 %. Besides, the difference in PF occurrence between FL and TP was affected by topographic position. At the mid-slope location, particularly in deeper soil layers (i.e., 40–80 cm), both FPF and PSWS in FL were significantly (p < 0.05) higher than those in TP. Conversely, no such differences were observed at the upslope or downslope location. These results reveal the limited development of PF at certain topographic positions in TP hillslope. Moreover, following the land-use conversion, the influence of rainfall on PF transitioned from quantity control to duration control, and the variety of soil properties affecting PF occurrence increased. These findings indicate that the deforestation for tea cultivation has weakened the rapid infiltration of soil water and altered the controlling factors over this process, which can provide valuable insights for land-use and water resource management in subtropical humid mountainous ecosystems.